From Sacred Ritual to Public Performance: Genealogical Transmission and Cultural Hybridity of the Gendong Dance in the Akit Community, Indonesia - Arbi, Arbi; Herlina, Herlina; Dewi, Eva; Hanafi, Imam (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study examines the transmission and transformation of the Gendong dance among the Akit community in Riau Province, focusing on how ritual knowledge and practices are sustained or disrupted without formal institutions. The research addresses the urgency of safeguarding this endangered intangible heritage, which has undergone functional shifts under modernization and socio-economic pressures. Employing a qualitative ethnographic approach, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using descriptive-interpretive methods informed by cultural sociology and anthropology. The findings reveal three key dynamics: (i) the transmission of the Gendong dance is primarily genealogical, reinforced by informal apprenticeship and ritualized knowledge such as prayers, chants, and taboos; (ii) its role has shifted from sacred purification rituals, notably in Bele Kampung, to public performances at civic celebrations and tourism events, entailing changes in choreography, duration, and media; and (iii) the community negotiates between maintaining sacred elements in limited ritual contexts and adapting performative aspects for modern audiences. These findings imply that cultural sustainability requires integrated strategies to balance preservation with adaptation, including educational inclusion, creative economy support, and digital documentation. The originality of this research lies in its focus on micro-level processes of genealogical transmission and cultural negotiation—an underexplored dimension in previous studies that primarily emphasized symbolic, ritual, or commodified aspects. This contribution enriches academic discourse on intangible heritage and practical frameworks for inclusive cultural policy.